The effect of FIFA-11 movements on the prevention of injuries to hearing-impaired football players - Açak, Mahmut; Karademir, Tamer; Acet, Mehmet; Coşkuner, Zeki (My University, 2013)
The efficacy of the FIFA-11 program for preventing injuries was examined with the purpose of decreasing the injuries of hearing-impaired football players. Two teams which play in the 1st League for the Turkish hearing-impaired, both in same group and from same geographical region, were chosen. The FIFA-11 program for the prevention of football injuries was applied on one of these teams. The second team was chosen as the control group. The control group continued its routine training throughout season. Their injury level was assessed using the Fysion Blesreg questionnaire form before and after the season. The injury incidence for the education group for 1000 hours of play was found to be 51.66, and it was found to be 92.98 for the control group. It was determined to be 17.22 for the education group and 30.99 for control group in training. Nine point four percent of the injuries received by the control group had appeared as a result of fights they had with their rivals after match. There are percentage differences between injury variations of the education group and the control group. The present study proves that regular applications such as FIFA-11 on hearing-impaired sportsmen can decrease the rate of injuries.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Deaf football players; Injury prevention; FIFA-11 program